Anti‐Violence Human Resource Management and Workplace Violence: Perspectives From Australian Aged Care Managers and Employees - Cavanagh, Jillian; Pariona‐Cabrera, Patricia; Bartram, Timothy; Meacham, Hannah (Human Resource Management, 2025)
ABSTRACT Incidents of workplace violence are commonplace against nurses and personal care assistants (PCAs) employed in aged care facilities. This article examines ways in which managers and human resource (HR) departments manage workplace violence. In this context, understanding anti‐violence human resource management (HRM) practices and other ways in which incidents of violence are managed may have important implications for workforce sustainability. Greenwood and Freeman's [Greenwood, M., & Freeman, R. E. (2011). Ethics and HRM: The Contribution of Stakeholder Theory. Business & Professional Ethics Journal , 269–292.] conceptual model of employee engagement and “ethical” HRM underpins this study by focusing on stakeholder engagement and stakeholder agency. We take a qualitative approach to examine workplace violence in aged care facilities in Australia by conducting semi‐structured interviews with 60 participants. We report on narratives of participants highlighting the unethical use of HRM as evidenced by a lack of anti‐violence HRM in aged care facilities. To encourage greater workforce sustainability, we argue that HR departments and managers need to behave ethically and better support the management and mitigation of workplace violence against workers in aged care facilities. Our paper provides new theoretical and practical insights into understanding the role of stakeholder engagement and stakeholder agency, and the moral treatment of employees through the development of anti‐violence HRM within the aged care context.